2013
DOI: 10.1155/2013/680821
|View full text |Cite
|
Sign up to set email alerts
|

TiO2‐SiO2/Ph‐POSS Functional Hybrids: Preparation and Characterisation

Abstract: The results of studies involving the innovative TiO2-SiO2/Ph-POSS hybrid were presented. An inorganic TiO2-SiO2oxide composite was precipitated from an emulsion media. The functionalisation of surface for the obtained composite was carried out with the use of TriSilanolPhenyl POSS (Ph-POSS) and a silane coupling agent—phenyltrimethoxysilane (PTMS). Electrokinetic and physicochemical as well as structural characteristics of obtained hybrids were evaluated. The zeta potential value has been determined, which pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The SiO 2 (17.2%)/TiO 2 _400 sample showed the lowest zeta potential (+14.6 mV). Our observations agree with those of Nowacka et al [51], who found that the zeta potential decreases with increasing pH value, confirming that the zeta potential value strongly depends on pH.…”
Section: Characterization Of the Photocatalystssupporting
confidence: 93%
“…The SiO 2 (17.2%)/TiO 2 _400 sample showed the lowest zeta potential (+14.6 mV). Our observations agree with those of Nowacka et al [51], who found that the zeta potential decreases with increasing pH value, confirming that the zeta potential value strongly depends on pH.…”
Section: Characterization Of the Photocatalystssupporting
confidence: 93%
“…The following characteristic IR signals were observed for the two silicate-surface-modified catalysts: 670 cm -1 , Ti-O-Ti asymmetric stretching; 1060 cm -1 , Si-O-Si symmetric stretching; 960 cm -1 Si-O-Ti stretching; 3750 cm -1 , SiO-H extending and a broadband 3700-3500 cm -1 corresponding to water adsorbed on catalysts. These signals have also been identified in SiO2-TiO2 hybrid spheres and sol-gel TiO2-SiO2 films [39,40]. FT IR spectrum of am-P25, am-P25-SiO2, am-TiO2, and am-TiO2-SiO2 are shown in Figure S3.…”
Section: Catalysts Characterizationmentioning
confidence: 72%
“…Table 1 presents the weight percentages of Ti and Si according to the quantities of TEOS used in the preparation. Figures 3, 4, and 5 show the SEM images, Tauc's equation using the DRS UV-vis spectra of the P25 powder and PET-1.0Si-P25, and the FT-IR spectra of PET, the P25-SiO2 powder, and PET-1.0Si-P25 with the corresponding assignment of signals, respectively [20,21]. The plot of (αhν) 2 versus the photoenergy (hν) of each catalyst shown the curve line using the Tauc's relation (Figure 4), which intercepted on the photoenergy as its bandgap energy.…”
Section: Film Preparation and Characterizationmentioning
confidence: 99%